Naskah-naskah Moloku Kie Raha: Suatu Tinjauan Umum - Titik Pudjiastuti (Manuskripta, 2016)
Moloku Kie Raha is a term used for referring the four local authorities in Maluku that known as Kolano: Ternate, Tidore, Bacan, dan Jailolo. As a key region in the shipping lanes during the "Silk Road" era, the presence of immigrants (Javanese, Chinese, Arab, and European) in the 14-17 centuries who brought their cultures and languages and interacted with local culture had established the local written culture. The scribe of the the Ternate sultanate said that since the past the palace also served as the scriptorium, which is where the hikayat, treaty, political documents, genealogy, and folklore which are associated with the sultanate, was written. This article is the result of codicological research that examines the physical manuscript as a focus. This research has inventoried the existence of 67 manuscripts of 12 owners that have been successfully recorded and digitized. When reading the content, the manuscripts were written about Islamic doctrines, king's letter, sufism order, hikayat, genealogy, history, laws of inheritance, horoscope, and levo-levo (amulet) while they are written in the Arabic and Jawi scripts in Arabic and Malay languages. --- Moloku Kie Raha adalah istilah untuk menyebut empat penguasa daerah di Maluku yang disebut kolano: Ternate, Tidore, Bacan, dan Jailolo. Sebagai sebuah titik penting dalam jalur pelayaran pada zaman ‘jalur sutra’, kehadiran orang asing (Jawa, Cina, Arab, dan Eropa) pada abad ke-14-17 yang membawa budaya dan bahasanya serta berinteraksi dengan budaya lokal telah membentuk budaya tulis setempat. Juru tulis kesultanan Ternate menyebutkan, bahwa sejak masa lalu istana juga berfungsi sebagai skriptorium, yakni tempat hikayat, perjanjian, dokumen politik, silsilah dan cerita rakyat yang berhubungan dengan kesultanan ditulis. Artikel ini merupakan hasil penelitian yang bersifat kodikologis dengan obyek kajian pada fisik naskahnya. Penelitian ini berhasil menelusuri keberadaan 67 naskah kuno dari 12 orang pemilik naskah yang berhasil didata dan didigitalkan. Ditilik dari isinya, naskah-naskah itu berisi tentang ajaran Islam, surat raja, tarekat, hikayat, silsilah, sejarah, hukum waris, primbon, dan levo-levo (ajimat) sedangkan teksnya ditulis dengan aksara Arab dan Jawi dalam bahasa Arab dan Melayu.